Karakterisasi Anggrek Jenis Phalaenopsis amboenensis J.J. Smith di Wilayah Resort Mallawa Taman Nasional Bantimurung Bulusaraung - Erwinda Erwinda; Andi Faridah Arsal; St. Fatmah Hiola (bionature, 2022)
Abstract. Resort Mallawa Bantimurung Bulusaraung National Park is a location where many orchids grow. This study aims to determine the type of orchid Phalaenopsis amboenensis J.J. Smith. This study uses the roaming method by conducting a search of the study area and documentation which includes taking pictures and morphological characterization as the basis for identifying orchid species. Orchid exploration was carried out at 4 locations with altitudes ranging from 400 m above sea level to 954 m above sea level. Based on the altitude where the Phaleonopsis amboenensis orchid was found at an altitude of 839 to 927. Based on the light intensity, it was found in semi-shaded conditions with monopodial growth type. Keywords: characterization, bantimurung bulusaraung national park area, phalaenopsis amboenensis j.j. smith, resort mallawa